Policy Change in Brazil: New Challenges for Policy Analysis in Latin America - Brasil, Felipe [UNESP]; Capella, Ana Claudia Niedhardt [UNESP]; Fagan, E. J. (Wiley-Blackwell, 2020)
From the emergence of punctuated equilibrium theory in the United States in the mid-1990s to the creation of the Comparative Agendas Project, scholars have predicted that punctuated equilibrium theory and related agenda-setting theories can be applied across all systems. Yet most of the literature to date has focused on Western countries. The Brazilian Agendas Project has now made data available on a wide range of policy inputs and outputs, the first such data available in Latin America. The objective of this article is introduce the data from the Brazilian project, justify the choices made in collecting and coding it, and present descriptive analyses on the dynamics of governmental attention toward different policy issues over time.
Keywords: Latin America; policy change; Brazil; punctuated equilibrium; agenda setting